1998
DOI: 10.1159/000023297
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin D Receptor Polymorphism Influence the Response of Bone to Brisk Walking in Postmenopausal Women?

Abstract: Vitamin D receptor (VDR) polymorphism may be a genetic factor affecting bone mineral density (BMD). This study examined the interaction of VDR genotype with the effect of an exercise intervention on bone measurements in UK postmenopausal women. 33 walkers, who completed 20.4 ± 3.9 (mean ± SD) min day–1 of brisk walking over 1 year, and 36 controls agreed to give DNA samples. BMD was measured at the lumbar spine, femoral neck and calcaneus by dual energy X-ray absorptiometry and broadband ultrasonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Studies of the associations between VDR genotype and physical activity also are limited, but have shown that people with the bb VDR genotype respond to physical activity in relationship to bone density more than those with the BB VDR genotype [52]. Another study showed that men who were inactive and had the BB VDR genotype were more likely to have higher fasting glucose levels than men with other VDR genotypes [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the associations between VDR genotype and physical activity also are limited, but have shown that people with the bb VDR genotype respond to physical activity in relationship to bone density more than those with the BB VDR genotype [52]. Another study showed that men who were inactive and had the BB VDR genotype were more likely to have higher fasting glucose levels than men with other VDR genotypes [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining VDR polymorphisms with energy balance and cancers of the colon and rectum have not been reported, thus support for examination of the possible association must come from other studies. Studies of bone mineral density and VDR gene have shown that those with the bb VDR genotype had a greater response to brisk walking than those with the BB VDR genotype [30]. Other studies, focusing primarily on bone density, suggest that physical activity may interact with VDR genotype to alter fasting glucose levels [31].…”
mentioning
confidence: 99%
“…Moreover, Blanchet et al 28 and Gentil et al 7 showed that the dominant genotype is associated with increased BMD in physically active women. Tsuritani et al 11 found that the recessive genotype is more responsive to exercise. These contradictions show that more studies are needed to confirm the interaction between VDR gene polymorphisms, physical and functional tests and BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tsuritani et al 11 found that the recessive allele is more responsive to physical exercise. Jarvinen et al 12 found no interaction between genetics and physical activity, demonstrating that the bone tissue benefited from physical activity regardless of VDR gene.…”
Section: Introductionmentioning
confidence: 99%
“…After adjusting for age and body mass index, the heritability of BUA is estimated to be 0.58 (95% confidence interval [CI], 0.41-0.75) vs 0.77 (95% CI, 0.63-0.91) for axial BMD or 0.63 for whole-body BMD (95% CI, 0.26-1.00) [16]. Genetic variations in calcitropic hormones, cytokines, their receptors, and their downstream target proteins, including the vitamin D receptor [17,18], osteocalcin [19], α 2 -HS-glycoprotein/fetuin [20], estrogen receptor-α [21], interleukin-6 [22], transforming growth factor (TGF)-β1 [23], methylene tetrahydrofolate reductase [24,25], osteoprotegerin [26], and type I collagen [27], have been correlated with changes in the QUS properties of bone.…”
Section: Quantitative Ultrasound and Genes That Regulate Bone Metabolismmentioning
confidence: 99%